Afterword: Middle Class Activism and Bangalore's Environmental Predicament - Carol Upadhya (Revue Internationale de Politique de Développement)
Carol Upadhya suggests that changes in Bangalore’s social composition and political economy have not only affected the consumption practices of its middle classes, but have also shaped public perception of urban environmental problems as well as the modes of civic engagement documented in this special e-issue. India’s new consumer and public cultures are increasingly centred on these new middle classes, whose lifestyles reflect a tension between a rising consumerist culture and growing environmental awareness. While civic activism and initiatives around waste management in Bangalore are aimed at more sustainable urban management, they fail to address the need for more equitable and democratic mechanisms of public governance. Middle-class actors rarely raise the twin questions of municipal governance and local democracy that must be addressed if long-term solutions to environmental degradation are to be found. This afterword, therefore, invites us to analyse the political economy of consumption and waste that links it to a larger critique of the ‘world-city’ agenda that underlies Bangalore’s development planning.